Newborn literacy program effective in increasing maternal engagement in literacy activities: an observational cohort study - Veldhuijzen van Zanten Stephanie; Coates Chrystal; Hervas-Malo Marilou; McGrath Patrick J (BMC Pediatrics, 2012)
Abstract Background Literacy is important for success in school and in adulthood. Book-gift programs at birth exist to help develop these foundations early on. The effectiveness of the Read to Me! Nova Scotia Family Literacy Program (a program where books and literacy materials are given to families in hospital when their baby is born) on the duration and frequency with which mothers engage in reading and other literacy based activities with their newborns was assessed. Methods An observational cohort study design was used. Mothers of babies who received the Read to Me! package in Nova Scotia born between January-August 2006 made up the intervention group (N = 1051). Mothers of babies born in Prince Edward Island between December 2006 and March 2008 made up the control group (N = 279) and did not receive any literacy package when their baby was born. A phone questionnaire was conducted consisting of questions regarding frequency and duration of maternal engagement in language and literacy-based activities with their infants. These activities included reading, singing, talking, listening to CDs and the radio and watching TV. Babies were aged 0–10 months at the time of the interview. Results Mothers who received the Read to Me! literacy package spent significantly more time reading to their babies, 17.9 ± 17.6 min/day compared to controls 12.6 ± 10.7 min/day, (p < 0.0001). Conclusions Read to Me! may be an inexpensive, easy to administer and effective intervention which results in increased shared reading of mothers and their newborns.